The Effect of Plant Growth Regulator on Duku (Lansium domesticum Corr.) Flower for Fruit Formation - Susilawati Susilawati; Lidwina Ninik S.; Mery Hasmeda; Irmawati Irmawati (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2017)
Plant growth regulators have a significant impact on increasing both quality and quantity of plant yield for either mixed or separated application. The research was aimed to identify the effect of spraying plant growth regulators on duku flowers for fruit formation. The research was conducted from December 2014 to May 2015 in Sijacarana Local Technical Implementation Unit (UPTD) of Propagation, South Sumatra Province in Ogan Komering Ulu (OKU) Timur Regency. Duku tree used was 15 years old with the height around 10 meter. Complete Randomized Design was used with 3 replications where duku trees as the replicates. The spraying consisted of 3 single plant growth regulator treatments and 6 mixed treatments which were P1 (BAP 300 mg.L-1), P2 (NAA 300 mg.L-1), P3 (GA3 300 mg.L-1), P4 (BAP 100 mg. L-1 + GA3 200 mg.L-1), P5 (BAP 200 mg.L-1 + GA3 100 mg.L-1), P6 (BAP 150 mg.L-1 + GA3 150 mg.L-1), P7 (NAA 100 mg.L-1 + GA3 200 mg.L-1), P8 (NAA 200 mg.L-1 + GA3 100 mg.L-1), P9 (NAA 150 mg.L-1 + GA3 150 mg.L-1). Spraying was applied twice with a half dosage for each application. First application was performed about one month after flowering, and the second was one and a half month after flowering. Data were analyzed using analysis of variance and least significance difference at α 5%. The measurement of parameters were carried after harvest or 3 months after treatment. Results showed that plant growth regulator positively affected duku fruit formation. GA3 treatment then was considered as the best treatment as it had a unison in fruit maturity, the highest number of fruit per bunch, weight per fruit and total fruit weight per bunch, and had the lowest number of green fruit and seed per fruit.